Trade Based Money Laundering Evidence from Indonesia: Cigarette Import Customs Smuggling and Money Laundering - Aditya Subur Purwana; Muhammad Anshar Syamsuddin; Mardiansyah Mardiansyah (Educoretax, 2023)
Public-Private Partnership (PPP) is an instrument to strengthen synergy in eradicating money laundering and other economic crimes launched by the government of the Republic of Indonesia, with 3 (three) main priorities to be handled, namely trade-based money laundering (TBML), narcotics, and business email compromise (BEC). The Financial Action Task Force (FATF) defines Trade Based Money Laundering as the process of disguising the proceeds of crime and transferring value through the use of trade transactions in an attempt to legitimize its illegitimate origin. Customs is everything related to the supervision of the traffic of goods entering or leaving the customs area as well as the collection of import and export duties, the supervision of which is carried out by the Directorate General of Customs and Excise (DGCE). In import customs activities, importers are obliged to fulfill customs obligations, one of which is the inward manifest. The research aims to provide an overview of money laundering and violations in the Customs Sector. Using secondary data from 2019 to 2023 and primary data through interviews, to answer the research objectives using qualitative methods based on court decisions. The research results show that the mode of money laundering violations in the customs sector is smuggling of unmanifest imports of cigarettes without excise stamps attached using the ship-to-ship mode. In laundering money from the crime, the perpetrator hides or disguises the proceeds from the crime of selling cigarettes that are not attached with excise stamps by placing the money from cigarette sales in several accounts in the perpetrator's name and in other names as well as in other forms of assets. Research suggestions, violations in the customs sector that have sufficient evidence of a crime, apart from being able to investigate predicate crimes, money laundering investigations can be carried out so that asset recovery can be carried out and optimizing the PPP scheme in cracking down on money laundering.